Improvements in lung function with budesonide/glycopyrrolate/formoterol fumarate metered dose inhaler versus dual therapies in patients with COPD: a sub-study of the ETHOS trial. (August 2021) - Rabe, Klaus F.; Martinez, Fernando J.; Singh, Dave; Trivedi, Roopa; Jenkins, Martin; Darken, Patrick; Aurivillius, Magnus; Dorinsky, Paul
Background: In the phase III, 52-week ETHOS study in patients with moderate to very severe chronic obstructive pulmonary disease (COPD), triple therapy with budesonide/glycopyrrolate/formoterol fumarate (BGF), at two inhaled corticosteroid dose levels, resulted in significantly lower moderate/severe exacerbation rates versus glycopyrrolate/formoterol fumarate (GFF) and budesonide/formoterol fumarate (BFF). Here, we report results from the ETHOS pulmonary function test (PFT) sub-study, which assessed lung function in a subset of ETHOS patients. Methods: ETHOS (NCT02465567) was a randomized, double-blind, multi-center, parallel-group study in patients with moderate to very severe COPD who had experienced ⩾1 moderate/severe exacerbation in the previous year. Patients received BGF 320/18/9.6 µg, BGF 160/18/9.6 μg, GFF 18/9.6 µg, or BFF 320/9.6 µg twice daily via a single metered dose Aerosphere inhaler for 52 weeks. A subset of patients participated in the 4-hour PFT sub-study; primary endpoints were change from baseline in morning pre-dose trough forced expiratory volume in one second (FEV1 ) versus GFF and FEV1 area under the curve from 0 to 4 hours (AUC0–4 ) versus BFF at week 24. Results: The PFT modified intent-to-treat population included 3088 patients (mean age 64.4 years; mean reversibility post-albuterol 16.7%; mean post-albuterol FEV1 % predicted 42.8). BGF 320/18/9.6 µg and 160/18/9.6 µg significantly improved morning pre-dose trough FEV1 at week 24 versus GFF ( p ⩽ 0.0035 for both). Improvements in trough FEV1 were also observed at week 52 for BGF 320/18/9.6 µg and 160/18/9.6 µg versus GFF ( p ⩽ 0.0005 for both). For FEV1 AUC0–4 at week 24, BGF 320/18/9.6 µg and 160/18/9.6 µg showed significant improvements versus BFF ( p < 0.0001 for both). Improvements were maintained at week 52 ( p < 0.0001). Conclusions: BGF 320/18/9.6 µg and 160/18/9.6 µg significantly improved trough FEV1 versus GFF and FEV1 AUC0–4 versus BFF at week 24. The lung function benefits with both doses of BGF were maintained following 52 weeks of treatment. The reviews of this paper are available via the supplemental material section.